Towards Inclusive, Participatory Peer Tutor Development in Higher Education - Clarence, Sherran (Critical Studies in Teaching and Learning, 2023)
Peer tutoring has a long history in academic support spaces in universities, such as writing centres and supplemental instruction programmes. Small group peer tutoring has moved increasingly into ‘mainstream’ teaching and learning, and has become an academic necessity in these spaces. The nature of student-tutor engagements in these spaces is about sharing and co-constructing knowledge, and developing more independent student learners. Yet, tutor development and training tends to under-prepare peer tutors to create participatory, inclusive tutorial environments. This paper argues for tutor development itself to model participatory, inclusive ,and development practices, such that tutors learn from being part of the training process how to improve their practice. Drawing on qualitative data from a three-year project at a traditional, historically black South African university, this paper shows how such an approach yields benefits for tutors that include building knowledge about tutoring that overtly includes tutors’ existing knowledge and experiences. Ultimately, a more inclusive approach to tutor development has a strong likelihood of changing tutoring praxis, making tutorials more participatory, inclusive, and shared spaces for learning.